Impact of STEAM Robotics Laboratories on Students’ Higher Order Thinking Skills - Kainat , Sohaib Sultan (JSE, 2023)
STEAM robotics laboratories are frequently used in different schools of private sector in Pakistan to engage student’s effectively in learning and make them higher order thinkers. Higher order thinking skills are thinking logically, critically and reflectively. While computational thinking and problem solving are also higher order thinking skills. The objectives of this research were; to investigate the influence of robotics laboratory on the thinking skills of students; to examine the impact of STEAM robotics laboratory to develop the higher order thinking skills in students.